Get real with moment / Wan Nurul Fatihah Wan Ismail - Wan Ismail, Wan Nurul Fatihah (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
Academy of Language Studies, UiTM Perak Branch, Tapah Campus organized a programme on mobile apps development which began with a workshop in the morning. Two facilitators for the workshop were invited from Kolej Universiti Islam Antarabangsa Selangor to guide and teach the participants in developing a mobile app. A total of 53 participants from UiTM, Politeknik Ungku Omar, Kolej Komuniti Bagan Serai, Kolej Komuniti Taiping, Kolej Komuniti Pasir Salak, Institut Pendidikan Guru Ipoh and Institut Pendidikan Guru Darul Aman were guided on the steps to develop a mobile app by using a website. The facilitators guided the participants using a hands-on approach during the workshop where they were able to experiment using the website to create a mobile app based on their needs and creativity.